Роль і значення трудових ресурсів у забезпеченні ефективності роботи будівельного підприємства - Омельяненко, О. П. (Ways to Improve Construction Efficiency, 2014)
The article analyzes the role and importance of human resources to ensure the efficiency of the construction company.